The Effect Of Career Development And Use Of Information Technology On Employee Performance At The Service Of Population And Civil Registration Tasikmalaya City: - Ramanda, Amelia; Karmila, Mila; Sutrisna, Arga (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to determine the simultaneous or partial influence of Career Development variables, Use of Information Technology on Employee Performance. The research method used was a quantitative method with a survey approach of 47 employees of the Tasikmalaya city population and civil registration service. The types of data used are primary data and secondary data. The data analysis technique used is multiple regression analysis using SPSS 23. The results of this test prove that Career Development and Use of Information Technology simultaneously have a significant effect on Employee Performance. Partial Career Development has no effect on Employee Performance. The use of Information Technology partially has a significant effect on Employee Performance.